(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2023)
This research attempts to assess the priorities and difficulties of India’s G20 Presidency,identify the actions India may take to further the goals it has set, and assess the potential effects ofIndia’s G20 Presidency on global economic and financial issues. The study used a descriptive researchapproach based on an existing literature review to evaluate the goals and difficulties of India’s G20Presidency. The analysis was based on secondary sources, such as news, articles from academicjournals, and government documents about the G20 and India’s participation in this organisation.According to the study findings, India’s G20 Presidency goals included environmental protection,financing for climate change, rapid and inclusive growth, advancement of the SDGs, priority for womenleddevelopment, technological change, multilateral institutions for the twenty-first century, and health.The study also discovered that there were numerous obstacles to India’s G20 presidency, includingChina’s aggression towards Taiwan, the escalating food and energy crises brought on by the conflict inthe Ukraine and Russia, North Korea’s continued hostility, the emergence of trade threats in the Indo-Pacific region, the global economic slowdown and growing environmental concerns.